Hybrid amorphous TiO2/polymer nanomaterials trigger apoptosis of pediatric cancer cells upon ultrasound irradiation. (December 2021) - Pariente, A.; Peled, E.; Zlotver, I.; Sosnik, A.
Abstract: Sonodynamic therapy is a cost-effective, minimally invasive and localized anticancer therapy based on the in situ generation of reactive oxygen species by combining low-intensity ultrasound (US), oxygen, and a sonosensitizer and it minimizes systemic toxicity. In this work, we initially study the effect of poly(ethylene oxide)-poly(propylene oxide) (PEO-PPO) block copolymers of different architecture, molecular weight, and hydrophilic-lipophilic balance on the size, size distribution and morphology of hybrid amorphous TiO2 /polymer sono-responsive nanoparticles (NPs) produced by a sol-gel process that comprises the synthesis and aging of a Ti(IV)-acetone oxo-organo complex, its mixing with the PEO-PPO block copolymer and their nanoprecipitation in water. Regardless of the PEO-PPO block copolymer used in the synthesis, the properties of the hybrid NPs are governed by the age of the oxo-organo complex. At the same time, we show the ability to incorporate a variety of amphiphiles with different hydrophilic-lipophilic balance, and thus, different encapsulation capacities of hydrophobic cargos. Morphological analysis by high-resolution–transmission electron microscopy shows that all the NPs are rounded. Next, we demonstrate that these hybrid NPs induce the formation of reactive oxygen species upon irradiation with the therapeutic US. In addition, they exhibit good compatibility and uptake by the Rh30 cell line, a model of rhabdomyosarcoma (a pediatric tumor of connective tissue) and do not cause significant hemolysis upon exposure of up to 24 h. Finally, we investigate the pathway by which these nanomaterials kill Rh30 cells by using annexin-V/propidium iodide staining and flow cytometry and demonstrate that, upon US induction, they trigger cell apoptosis. To the best of our knowledge, this is the first work reporting on the sono-responsive performance of an amorphous TiO2 -based nanomaterial and its potential application in the sonodynamic therapy of cancer. Graphical abstract: Image 1 Highlights: Hybrid amorphous TiO2 /poly(ethylene oxide)-poly(propylene oxide) block copolymer nanoparticles are synthesized. Nanoparticles induce the formation of reactive oxygen species upon irradiation with the therapeutic ultrasound. Nanoparticles exhibit good cell compatibility and hemocompatibility in vitro . Nanoparticles are uptaken by the Rh30 cell line. Upon ultrasound induction, nanoparticles trigger cancer cell apoptosis.